If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 + 3x = -12 Solving -9 + 3x = -12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 3x = -12 + 9 Combine like terms: -9 + 9 = 0 0 + 3x = -12 + 9 3x = -12 + 9 Combine like terms: -12 + 9 = -3 3x = -3 Divide each side by '3'. x = -1 Simplifying x = -1
| 3n/11=10 | | 3+4(7-9)= | | 8x+13x=17 | | 3+4(7-9)2= | | 28=-2m | | -3/5=-7/10x | | 5(-4x+9)=165 | | y=0(2)2 | | 3+4(7-9)*2= | | 24=3e | | 6-3x=5x-10x+5 | | 25+11/12y=47 | | 1/3(6X-2)=5 | | 43+19+(-6)= | | w-1/4=w+3/3 | | 7(5x-5)=0 | | 4y-7=-10+y | | 5(c-7)=5 | | 2x/2=105 | | 2x+4=105 | | 2(s+4)=16 | | x=35-6y | | 17*15/(17*15) | | d/2+20-13=42 | | -3(4x+4)=-12solve | | 1/3(3x) | | x+6x-8=13 | | 2125=25p+15(20-p) | | 2x-2=105 | | 4+3z-1=9z+3-4z | | 21.25=0.25p+1.5(20-p) | | -5/6/(-5/6) |